2008
DOI: 10.2214/ajr.07.3419
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hepatic Adenomas Associated with Liver Steatosis at CT and MRI: A Case-Control Study

Abstract: Hepatic adenomas occur more frequently and more often are multiple in patients with hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Another study [32] found that hepatic steatosis as measured by CT scan was present in 82% of patients with multiple HCAs as compared with 58% of patients with single HCA and 29% in a control group of patients with hemangioma. These series highlight the association between HCAs (in particular multiple HCAs) and steatosis and suggest potential factors that drive both steatosis and formation of HCAs.…”
Section: Introductionmentioning
confidence: 99%
“…Another study [32] found that hepatic steatosis as measured by CT scan was present in 82% of patients with multiple HCAs as compared with 58% of patients with single HCA and 29% in a control group of patients with hemangioma. These series highlight the association between HCAs (in particular multiple HCAs) and steatosis and suggest potential factors that drive both steatosis and formation of HCAs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies reported a gender distribution in favour of female patients (74,75) and an association with OC use, glycogenosis, diabetes, high BMI, germline mutations of HNF-1a (L-FABP-negative HCA, a subgroup that seems to be associated with steatotis), non-alcoholic fatty liver disease and patients who undergo a Fontan procedure (8,10,35,74,76,77). Eighteen per cent of patients with LA showed steatosis in non-tumoural tissue which affects the management of patients with LA as liver steatosis has an impact on the outcome of liver surgery (75,78). Several other authors reported or suggested an increased incidence of multiple adenomas ( 2) in the setting of liver steatosis (11,62,77,78).…”
Section: Multiple Hepatocellular Adenoma and Liver Adenomatosismentioning
confidence: 99%
“…6 Hepatic adenomatosis can be seen in either sex with or without oral contraceptive use 5 ; other risk factors for adenoma include glycogen storage disease and hepatic steatosis. 7 In addition, adenoma formation may be associated with germ-line HNF1A (hepatocyte nuclear factor 1α) gene mutations. 5,8,9 Risk of complication in both HA and adenomatosis is related to the size of the largest lesion and underlying histopathological subtype.…”
Section: Introductionmentioning
confidence: 99%